Epstein-Barr virus (EBV) DNAemia in saliva of viral encephalitis and nasopharyngeal carcinoma patients - Nanditha Srinivasan; Ramya Barani; M Manickavasagan; Padma Srikanth (Indian Journal of Pathology and Microbiology)
Epstein-Barr virus (EBV) is a lymphotropic virus that causes diseases ranging from a flu-like illness called infectious mononucleosis to nasopharyngeal carcinoma, Burkitt’s lymphoma, and central nervous system (CNS) infection. Detection of EBV DNA is usually done using whole blood samples taken from the patients. We undertook the detection of EBV in blood, cerebrospinal fluid (CSF), and saliva by real-time quantitative PCR in two patients, one with a history of nasopharyngeal carcinoma, and the other having a case of viral encephalitis. EBV was detected only in saliva, whole blood in both patients, and CSF in the second case tested negative. This case series illustrates the importance of testing for EBV DNAemia in saliva by real-time polymerase chain reaction (PCR) to rule in a diagnosis of EBV.